2020
DOI: 10.1080/14616696.2020.1827447
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Covid-19 pandemic on ethnic discrimination on the housing market

Abstract: This explorative study examines the impact of the Covid-19 pandemic on ethnic discrimination. By means of 482 pairwise matched correspondence tests in pre-Covid times and 440 tests in Covid times, we examine discrimination against candidates of Maghrebian and Congolese origin on the housing market of a metropolitan city in Belgium. While the absolute invitation rates decreased for both Maghrebian and Belgian candidates at almost the same pace in Covid times, the relative net rate of discrimination of Maghrebia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
1
22
2
Order By: Relevance
“…In Europe, Verhaeghe and Ghekiere [9] examined the impact of the COVID-19 pandemic on ethnic discrimination in the housing market of a metropolitan city in Belgium and found that the effects of COVID-19 on discrimination were different for different ethnic groups. Marona and Tomal [10] found that the COVID-19 pandemic had a considerable impact upon the workflow of real estate brokers and their clients' attitudes in the city of Krakow, Poland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Europe, Verhaeghe and Ghekiere [9] examined the impact of the COVID-19 pandemic on ethnic discrimination in the housing market of a metropolitan city in Belgium and found that the effects of COVID-19 on discrimination were different for different ethnic groups. Marona and Tomal [10] found that the COVID-19 pandemic had a considerable impact upon the workflow of real estate brokers and their clients' attitudes in the city of Krakow, Poland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors note that by February 2020, COVID-19 infections start to dominate newspaper coverage of stock market volatility and newspaper discussions on economic policy uncertainty. In March 2020, COVID-19 developments receive attention in more than 90% of all newspaper discussions of market volatility and policy uncertainty.8 By implementing a difference-in-differences setting,Verhaeghe and Ghekiere (2020) show how ethnic discrimination in a Belgian city's housing market increases during the COVID-19 pandemic. The authors identify lower income levels as one possible reason for this discrimination.…”
mentioning
confidence: 99%
“…These financial burdens also cover the costs directly connected with health care and related medical or social services, as well as indirect costs, such as the loss of productivity and limited possibilities for development [19] (pp. [33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Premises Behind Including Housing Policy In European Union P...mentioning
confidence: 99%